2020
DOI: 10.3389/fphys.2020.00757
|View full text |Cite
|
Sign up to set email alerts
|

Programming of Renal Development and Chronic Disease in Adult Life

Abstract: Chronic kidney disease (CKD) can have an insidious onset because there is a gradual decline in nephron number throughout life. There may be no overt symptoms of renal dysfunction until about two thirds or more of the nephrons have been destroyed and glomerular filtration rate (GFR) falls to below 25% of normal (often in mid-late life) ( Martinez-Maldonaldo et al., 1992 ). Once End Stage Renal Disease (ESRD) has been reached, survival depends on renal replacement therapy (RRT). CKD causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 123 publications
1
18
0
Order By: Relevance
“…The HDAC activity measurement kit (K331) was purchased from BioVision (Milpitas, CA, USA). Ouabain (O3125), furosemide (F4381), histone type III-S (H5505), and PKAi (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) peptide (P7739) were purchased from Sigma-Aldrich (Saint Louis, MO, USA). Calphostin C (208725) was purchased from Calbiochem (San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HDAC activity measurement kit (K331) was purchased from BioVision (Milpitas, CA, USA). Ouabain (O3125), furosemide (F4381), histone type III-S (H5505), and PKAi (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) peptide (P7739) were purchased from Sigma-Aldrich (Saint Louis, MO, USA). Calphostin C (208725) was purchased from Calbiochem (San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The risk of prevalent morbidities aggravated by malnutrition, such as kidney and cardiovascular diseases, are frequently associated with alterations in the renin-angiotensin-aldosterone system (RAAS) [1][2][3]. In the last few decades, several studies tried to elucidate the mechanisms by which malnutrition-induced systemic and local RAAS upregulation -in different windows of development -alters renal and cardiac Na + metabolism, leading to diseases such as arterial hypertension and cardiorenal syndrome [4][5][6][7][8][9][10][11][12]. We have demonstrated that renal and cardiac Na + handling is compromised by chronic multifactorial malnutrition due to upregulation of the AT 1 R → PKC signaling pathway [8,9], culminating in the onset of arterial hypertension [8]; the effects resulting from RAAS activation were blocked by Losartan (Los), an antagonist of the type 1 angiotensin II (Ang II) receptors (AT 1 R), thus confirming the role of RAAS in the pathophysiology of malnutrition-induced renal and cardiovascular lesions.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have demonstrated that maternal obesity has a detrimental impact on the development of the cardiovascular, pulmonary, and renal system with subsequent risk for chronic diseases later in life, the impact of maternal obesity on liver development and liver growth remains elusive [ 11 , 12 ]. The liver acts as the central regulator of energy homeostasis by orchestrating numerous metabolic processes, e.g., glycolysis, gluconeogenesis, and fatty acid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from epidemiological studies and animal models has bolstered the paradigm of ‘developmental origins of health and disease’ over the past decades 1–4. It is now well established that the first 1000 days of life (ie, from conception to the age of 2 years) is a critical time window for developmental trajectory programming 5 6. Adverse disturbances that occurred during this period may lead to increased risks of chronic diseases across one’s lifespan or an epigenetic transgenerational inheritance of such risks 7–10.…”
Section: Introductionmentioning
confidence: 99%